Social Consequences of Transition and European Integration Processes in the Baltic States - Tiiu Paas (European Regional Science Association (ERSA), 2003)
The paper focuses on studying economic integration of the countries that are involved in the EU eastward enlargement process giving emphasis on international trade. The main feature characterizing the EU eastward enlargement processes is integration of national economies with different historical backgrounds and structures. Regionalism is an important issue in the policy agenda influencing adjustment processes with the EU enlargement of the current members (EU15) and the candidate countries (CC12). The regional integration effects as the deviations from the volume of trade predicted by the baseline gravity model are analyzed in the paper. The empirical results of the study allow us to conclude that the behaviour of bilateral trade flows within the countries involved in the EU eastward enlargement accords to the normal rules of gravitation, having statistically significant spatial biases caused by the trade relations between the Baltic Rim countries (the BR bias) and the border countries (the border bias). The results of the study allow us to prove the preposition that lagged bilateral trade flows are still significant in determining current trade. Past trade linkages adjust rather slowly to the new conditions of the EU eastward enlargement. The Baltic Rim countries' bilateral trade flows are among the countries involved in the EU eastward enlargement on average 2 times larger than trade flows outside the region after controlling for traditional gravitational forces and other regional dummies. The evidence of cross-border trade relations and Baltic Rim regional cooperation is stronger in the current EU members than in the candidate countries. The countries around the Baltic Sea benefit from the integration due to the synergetic effect of non-homogenous entities - the countries on different economic levels and with different historical ties. The lessons of the Baltic Sea region in integrating countries with different economic and political backgrounds are valuable in supporting the EU eastward enlargement and the reintegration of the new member countries into Europe. Keywords: EU enlargement, the Baltic Sea Region, integration, international trade, gravity models JEL: F15, C5, R15
Keywords: 330